2020
DOI: 10.3390/v12040427
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Genetic Diversity of Human Hepatitis B Virus in Southeast Asia, Australia and New Zealand

Abstract: The extent of whole genome diversity amongst hepatitis B virus (HBV) genotypes is not well described. This study aimed to update the current distribution of HBV types and to investigate mutation rates and nucleotide diversity between genotypes in Southeast Asia, Australia and New Zealand. We retrieved 930 human HBV complete genomes from these regions from the NCBI nucleotide database for genotyping, detection of potential recombination, serotype prediction, mutation identification and comparative genome analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…We found genotype C to be predominant, followed by genotypes B and D, then genotype A. This observation was consistent with previous findings that genotypes B and C are most prevalent in Australia, followed by genotypes A and D [ 17 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found genotype C to be predominant, followed by genotypes B and D, then genotype A. This observation was consistent with previous findings that genotypes B and C are most prevalent in Australia, followed by genotypes A and D [ 17 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study identified the polymerase and pre-surface/surface loci as the most genetically diverse regions along the HBV viral genome [ 47 ]. In this study we found two genetically diverse regions, nt103–203 and nt333–438, which appear to contain or overlap with sequences coding for two corresponding epitopes of HBsAg (AA51–70 and AA110–147 for wild-type HBsAg GQ183486) predicted by Rezaee et al (2016) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this hypothesis deserves more substance and should be confirmed by undertaking well-designed longitudinal or case-control studies. It is supported, however, by the low nucleotide diversity observed by Phan and coworkers [ 20 ].…”
Section: Genetic Variations Observed On Hbv Genotype I Genomementioning
confidence: 94%
“…The proportions of te ancestral genotypes for each HBV genotype I gene and product are given in Table 1 . Concerning the overall nucleotide diversity of genotype I, Phan and coworkers observed a lower amount of diversity here than in other Australasian HBV genotypes (A, B, C, and D) except between nucleotides 2500–2600 (terminal protein domain) [ 20 ].…”
Section: Genome Architecturementioning
confidence: 99%
“…Several publications describe or review the clinical relevance of HBV variants [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, whilst previous studies analyze the frequency of mutations in a certain genomic region, within selected populations or within specific genotypes [ 30 , 31 , 32 , 33 , 34 ], there is currently no comprehensive overview of the distribution of clinically relevant HBV variants between world regions or genotypes. However, this information could be useful to understand varying phenotypes of the different HBV genotypes and inform further optimization of diagnostic tests and treatment regimens.…”
Section: Introductionmentioning
confidence: 99%